Carbon Sequestration and Fruit Production Potential of Aonla (Emblica officinalis Gaertn) in Degraded Lands of Indian Sub-Himalayas - Rathore, A. C.; Mehta, H.; Singh, Charan; Mishra, P. K. (Indian Forester, 2017)
Production potential of aonla cultivars was evaluated during 1996-2010 on degraded wastelands for productivity and carbon sequestration at Indian Institute of Soil and Water conservation, Dehradun (Uttarakhand). Data revealed that Krishna cultivar was recorded maximum canopy volume(103.2 m3), followed by NA-7 (102.5 m3), Chakaiya, Kanchan, NA-10 and minimum with NA-6 (100.0 m3). Canopy volume was positively correlated with fruit yield of aonla recorded maximum fruit yield (18.5 t/ha) followed by Krishna (17.4 t/ha) and minimum with Chakaiya (16.1 t/ha) with significant differences. Carbon content in various components of aonla was analyzedand maximum was observed in stem (49.0%), roots (47.5%), branch (48.5%), twigs (47.3%), leaves (47.2%) and fruits (47.0%). Similarly, maximum carbon stock (23.8 and 23.5 Mg ha-1)and atmospheric carbon dioxide mitigation (87.2 and 86.3 Mg ha ) was recorded in Krishna and NA-7 cultivars of aonla with the minimum values of carbon stocks and carbon dioxide mitigation in case of NA-6 (19.6 and 71.8 Mg ha-1). SOC storage in soil depth (30 cm) after 15 years varied from 36.4 to 41.0 Mg ha-1 over initial value (20.3 Mg ha-1) among aonla cultivars.